دور حاضنات الأعمال في ترقية المؤسسات الناشئة Start-up: دراسة حالة - زايدي حكيم (University Eloued جامعة الوادي, 2022)
الملخص: تهدف هذه الدراسة لمعرفة دور حاضنات الأعمال في ترقية المؤسسات الناشئة، وذلك من خلال إسهام هذه الحاضنات في تطوير محيط المؤسسات الناشئة المحتضنة من خلال التكوين وبناء العلاقات، وكذا مدى مساهمتها في تطوير المؤسسة الناشئة ونجاحها ومدى قدرتها على الابتكار، بالإضافة إلى تطوير مهارات أصحاب هاته المؤسسات من خلال الاحتضان، وبهدف ذلك قامت هاته الدراسة بإجراء مجموعة من المقابلات مع مسؤولي أربع حاضنات (حاضنة سيدي عبد الله، حاضنة المسيلة، حاضنة خاصة بتبسة، حاضنة جامعة الوادي)، بالإضافة إلى طرح استبيان إلى أصحاب المؤسسات الناشئة المحتضنين في هاته الحاضنات الأربع حيث بلغت عينة الدراسة 171 مبحوثا. وبعد الدراسة الإحصائية والتحليل خلصت الدراسة إلى أن هناك دلالة إحصائية معنوية كبيرة لمساهمة حاضنات الأعمال في ترقية المؤسسات الناشئة المنتسبة بها وذلك على مستوى جميع أبعاد ومحاور الاستبيان، بالإضافة إلى أن الدراسة خلصت إلى أن هناك أثرا قويا لهاته الحاضنات من شأنه أن يحدث تغييرا معتبرا على نجاعة ونجاح المؤسسات الناشئة المحتضنة، وبالتالي يتبين أن النموذج المقترح للدراسة أثبت فعاليته ونجاحه، وأخيرا قمنا بتقديم مجموعة من التوصيات الهامة. This thesis aims to study the role of business incubators in the promotion of startups, in order to know to what extent these incubators contribute to the development of the environment of incubated startups, as well as to what extent they contribute to the development and success of the nascent company, in addition to developing the skills of the owners of these institutions through incubation, and for the purpose of this present The study conducted a series of interviews with the managers of four incubators (incubator Sidi Abdallah , Messila University incubator, Tébessa private incubator and El Oued University incubator), in addition to submitting a questionnaire to the owners of the startups incubated in these four incubators, where the study sample amounts to 171 respondents. After the statistical study and analysis, the research concluded that there is significant statistical significance for the contribution of business incubators to the promotion of startups affiliated with them at the level of all dimensions and axes of the questionnaire, in addition to this the study concluded that there is a strong impact of these incubators which would bring a significant change on the efficiency and success of the incubated startups, and the model proposed for the study was tested, because it has proven its effectiveness and success in measuring the phenomenon demonstrated Finally, the researcher made a set of important recommendations.
أطروحة دكتوراه
Keywords: حاضنات الأعمال; المؤسسات الناشئة; التكوين وبناء العلاقات; الابتكار; Business incubators; start-ups; training and networking; innovation